Linear Buckling Analysis and Comparative Study of Un-stiffened and Stiffened Composite Plate. (2018) - Ravi Kumar, P.; Gupta, Ganesh; Shamili, G.K.; Anitha, D.
Abstract: In engineering application, the use of stiffened plates made of composite structures have increased over the last few decades due to its high efficiency in terms of high stiffness to low weight and high strength. Generally physical structure of stiffened plates are subjected to compressive in-plane loading and a continuous increase of these load results in buckling which in terms causes structural failure. The present research was done a finite element analysis of stiffened and un-stiffened plates with three different types of composite materials have been carried out with a view to predicting the buckling load by software ANSYS 14.0 APDL. Analyses have been performed to investigate the effect of fibre orientation, length to thickness ratio with same layup, aspect ratio with different layup configuration and different cut-outs shape for un-stiffened plate and the effect of height, position, number of stiffener, different types of stiffener and transverse stiffener for stiffened plate on buckling load. It is concluded from the result that [0/90/45/-45] fibre configuration yields the highest load, as the length to thickness ratio increases the load decreases, as the aspect ratio increases the critical load increases and critical load decreases in presence of cut-outs. It has also been observed that by increasing the number of stiffener on the stiffened plate, buckling load goes on increasing, T shape stiffened plate sustain maximum buckling load and with single stiffener at the centre of plate by varying an height of stiffener after a certain value, it gives constant buckling load for all material.